Biological Characteristics of Umbilical Cord Mesenchymal Stem Cells and Its Therapeutic Potential for Hematological Disorders - Shang, Yufeng; Guan, Haotong; Zhou, Fuling (Frontiers in Cell and Developmental Biology, 2021)
Umbilical cord mesenchymal stem cells (UC-MSCs) are a class of multifunctional stem cells isolated and cultured from umbilical cord. They possessed the characteristics of highly self-renewal, multi-directional differentiation potential and low immunogenicity. Its application in the field of tissue engineering and gene therapy has achieved a series of results. Recent studies have confirmed their characteristics of inhibiting tumor cell proliferation and migration to nest of cancer. The ability of UC-MSCs to support hematopoietic microenvironment and suppress immune system suggests that they can improve engraftment after hematopoietic stem cell transplantation, which shows great potential in treatment of hematologic diseases. This article will focus on the latest advances in biological characteristics and mechanism of UC-MSCs in treatment of hematological diseases.